2003
DOI: 10.1021/jp030162s
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Thermal Chemistry of Nitroethane on Si(100)-2 × 1

Abstract: Surface chemistry of nitroethane on Si(100)-2 × 1 has been investigated using multiple internal reflection Fourier transform infrared spectroscopy (MIR-FTIR), Auger electron spectroscopy (AES), and thermal desorption mass spectrometry. Molecular adsorption of nitroethane at submonolayer coverages dominates at cryogenic temperatures (95 K). As the surface temperature is increased to 140 K, chemical reaction involving nitro group occurs, whereas the ethyl entity remains intact. Similar behavior is observed for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The 263 K desorption peak shifted to 285 K for higher doses but was clearly distinguishable from the multilayer desorption reported at 185 K for 12.5 L dose [119]. This behavior is very similar to that reported by Teplyakov group for vinyltrimethylsilane [224], nitroalkanes [227] and nitrobenzene [224]. In all those cases, chemisorption competes with desorption; however, if the adsorbates reach the chemisorbed state, the process is irreversible since complex thermal chemistry starts as the surface is being heated.…”
Section: Diketones: Keto-enol Equilibrium As a Factorsupporting
confidence: 85%
See 1 more Smart Citation
“…The 263 K desorption peak shifted to 285 K for higher doses but was clearly distinguishable from the multilayer desorption reported at 185 K for 12.5 L dose [119]. This behavior is very similar to that reported by Teplyakov group for vinyltrimethylsilane [224], nitroalkanes [227] and nitrobenzene [224]. In all those cases, chemisorption competes with desorption; however, if the adsorbates reach the chemisorbed state, the process is irreversible since complex thermal chemistry starts as the surface is being heated.…”
Section: Diketones: Keto-enol Equilibrium As a Factorsupporting
confidence: 85%
“…3.8 [225,226]. Similar to simpler molecules, nitromethane and nitroethane, that were studied both theoretically and experimentally [164,[227][228][229], nitrobenzene was proposed to easily form this initial adduct and this first reaction step was to be followed by a series of steps leading to the migration of both oxygen atoms into the silicon backbond. A detailed study of this process revealed that despite the fact that all these steps occur downhill compared to the reactants (nitrobenzene and a Si(100)-2×1 surface), substantial reaction barriers may play a significant role in surface processes [226] as several intermediates, including the initial five-member adduct have been observed at room temperature.…”
Section: Functionalized Aromaticsmentioning
confidence: 99%
“…Our group has been working on this approach for over a decade. We initially focused on the reactions of nitroalkanes, including nitroethane and nitromethane, on a clean Si(100)-2 × 1 surface 52 in UHV. Both nitroethane and nitromethane undergo a 1,3 cycloaddition reaction on this surface at room temperature, and this initial attachment is followed by subsurface oxygen migration that can be promoted at elevated temperatures.…”
Section: Amines On Clean Silicon In Uhvmentioning
confidence: 99%
“…The clean (100) surfaces of silicon and germanium are characterized by rows of asymmetrically tilted dimers, which can be used as a template to modify the surface using controlled reactions with organic molecules. Recently, in an attempt to create a robust and chemically stable organic–inorganic interface, a number of studies have focused on grafting nitrogen-containing molecules onto silicon and germanium. The chemisorption of primary and secondary amines on Si(100) generally begins with the nitrogen atom forming a dative bond with the down-buckled atom of a silicon dimer, followed by N–H dissociation and the transfer of the hydrogen atom to a nearby up-buckled silicon atom. , The N–H dissociation step is governed by the properties of this datively bonded species, as the dative bond weakens the N–H bond and increases the nucleophilicity of the up-buckled silicon atom . In contrast to the Si(100) surface, primary and secondary amines on the Ge(100) surface typically form stable datively bonded species without undergoing N–H dissociation at room temperature.…”
Section: Introductionmentioning
confidence: 99%